Pelabelan 0-Anti Ajaib dan 2-Anti Ajaib untuk Graf Tangga L - Quinoza Guvil -; Roni Tri Putra (Jurnal Ilmiah Poli Rekayasa, 2016)
For a connected graph  and a subset  of   . For a vertex  the distance betwen  and  is . For an ordered k-partition of ,  the representation of   with respect to  is    The k-partition  is a resolving partition if  are distinct for every  The minimum k for which there is a resolving partition of   is the partition dimension of   In this paper will shown resolving partition of  connected graph order  where  is a bipartite graph. Then it is shown dimension partition of bipartite graph, are pd(Kst)=n-1